The Study of Service Quality and Relationship Marketing for Engaging Hotels Customer Loyalty - Shabrina Prameka, Adelia (KnE Social Sciences, 2020)
The purpose of this study is to analyze the effect between service quality towards customer loyalty through relationship marketing as intervening in four-star hotel services. Structural Equation Modeling (SEM) is used for analyzing the effect among service quality, relationship marketing and customer loyalty. The result shows there are relations’ effects between service quality on customer loyalty directly and indirectly, how service quality and relationship marketing can engage the customer loyalty hotels. When the guests have a good experience of leisure, they become loyal customer, if hotels provider can engage them using a relationship-marketing program also, not only satisfied with hotel good quality services. Another result shows that service quality is a key direct indicator as measurements of hotels provider to provide the good leisure services and as an experience desired when customer book a hotel for stay. Keywords: Service quality, relationship marketing, customer loyalty, hotel services, loyalty program